Enhancement of conventional concrete mix designs for sensible thermal energy storage applications. (May 2023) - Wang, Shuoyu; Abdulridha, Ahmed; Naito, Clay; Quiel, Spencer; Suleiman, Muhannad; Romero, Carlos; Neti, Sudhakar
Abstract: The study examines twenty-nine different concrete mix designs with varying constituents to improve thermal performance for energy storage at elevated temperatures up to 420 °C. Effects of variables including the type and volumetric percentage of coarse and fine aggregates, the type and replacement content of supplemental cementitious materials, water-to-cement ratio, the type and quantity of steel fiber reinforcement, and the inclusion of iron oxide powder are experimentally investigated by measuring the mechanical and thermal properties of each mix, with the overall goal of enhancing thermal performance and mitigating mechanical degradation for thermal energy storage (TES) applications. It is found that the use of siliceous aggregate with a high volumetric percentage produces the highest improvement (23 %–37 % at elevated temperatures) of concrete thermal conductivity, while silica fume replacement of Type I cement provides the highest improvement (4 %–8 % at elevated temperatures) of concrete specific heat. To simulate the operation of a TES system, thermal cycling was conducted to examine the change in concrete properties as a function of repetitive heating (during and after 50 total cycles to 420 °C). Based on the results of testing, concrete mix designs with high aggregate percentages (up to 72 % by volume), siliceous coarse aggregate, silica fume replacement of Type I cement (15 % by weight), and steel fiber reinforcement (up to 2 % by volume) facilitate enhanced TES performance by providing consistent thermal conductivity of ~2.2 W/m·K and specific heat of ~3.2 MJ/m 3 ·K under cyclic high temperature exposure. Highlights: Conventional concrete mixes with common constituents is tailored for deployment in sensible-heat thermal energy storage systems. Siliceous aggregate, high aggregate content, low water-to-cement ratio, partial cement replacement with silica fume and high steel fiber content produce superior thermal conductivity and specific heat in 280–420 °C TES conditions. Enhanced concrete mix exhibits stable thermal and mechanical performance after 50 TES-simulated thermal cycles.